2019
DOI: 10.1515/gps-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of palladium nanoparticles using guar gum as stabilizer and their applications as catalyst in reduction reactions and degradation of azo dyes

Abstract: AbstractPalladium is very expensive metal and has numerous applications especially as a versatile hydrogenation and dehydrogenation catalyst for chemical reactions. The main hurdle in its wide use is the high materials cost. In the present study a cost effective palladium nano catalyst was prepared using the green method of synthesis with guar gum as capping and reducing agent. The formations of palladium nanoparticles were confirmed by UV-spectrophotometer while for morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…In addition, Pd NPs were fabricated via ultrasonication of Andean blackberry leaf extract and were used for photocatalytic degradation of methylene blue. 23 Rao et al 24 reported enhanced photocatalytic degradation of bisphenol A by Pd/PdO/β-Bi 2 O 3 microspheres and M. A. Khan's research team 25 used guar gum as stabilizer to synthesize Pd NPs and applied the Pd NPs as catalysts for the degradation of azo dyes. However, these methods are complicated and difficult for synthesizing Pd NPs and some require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pd NPs were fabricated via ultrasonication of Andean blackberry leaf extract and were used for photocatalytic degradation of methylene blue. 23 Rao et al 24 reported enhanced photocatalytic degradation of bisphenol A by Pd/PdO/β-Bi 2 O 3 microspheres and M. A. Khan's research team 25 used guar gum as stabilizer to synthesize Pd NPs and applied the Pd NPs as catalysts for the degradation of azo dyes. However, these methods are complicated and difficult for synthesizing Pd NPs and some require sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 2026 and 2121 cm -1 are assigned to weakly bonded water molecules (O-H, H-O-H), while that at 1640 cm -1 can be linked to the H-O-H weakly bonded water molecules . The peak at 1014 cm -1 can be directly assigned to the C-O bond of carbonyl and carboxylate in GG (Anjum et al 2020). The peak at 1375 cm -1 can be associated with C-H bending of aldehyde.…”
Section: Natural Soil and Additivesmentioning
confidence: 99%
“…The peak at 3690 cm -1 is assigned to the strongly bonded water molecules (H-O-H) due to the hydroxylation of the GG to produce hydro-gels. Moreover, the peak at 1002 cm -1 is directly linked to the C-O bonds of the carbonyl and carboxylate groups, which occur in GG (Anjum et al 2020). These nuances provide evidence of gelation in the GG-stabilized soil.…”
Section: Stabilized Soilmentioning
confidence: 99%
“…This characteristic is important since it shows their reactivity in an environment that surrounds them. PdNPs works as an electron acceptor in the presence of H 2 in a catalytic reaction [64]. These reaction mechanisms could be involved in the toxicity mechanisms with different cell types.…”
Section: Nanoparticles Reactivity Characterizationmentioning
confidence: 99%